Rancang Model Ontologi Representasi Pengetahuan Kuliner Tradisional Kabupaten Bangli, Bali - Celia Maureen Chandra; Agus Muliantara (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
The Province of Bali is a preferred tourist destination in Indonesia, including one of the developing tourist areas, Bangli Regency. The tourism development in Bangli is closely linked to traditional cuisine as a key attraction. However, in preserving the traditional cuisine, it is evident that many residents lack in-depth knowledge about the variety of Bangli’s traditional dishes. This research aims to develop an ontology model representing the traditional culinary knowledge of Bangli Regency using Methontology method. The implementation, conducted using Protégé software, resulted in 6 classes, 8 object properties, 5 data properties, and 55 individuals. The ontology was evaluated using the Ontology Quality Analysis (OntoQA) method with schema metrics techniques, including RR, IR, and AR measurements. The evaluation revealed that the ontology has a high diversity of information and specific information representation, though the amount of information provided is still limited. With these promising results, the constructed ontology is expected to effectively represent the knowledge of traditional Bangli cuisine and serve as a foundation for developing an information system that facilitates access to this knowledge, thereby supporting its preservation.